The process of adoption of non-Muslim babies in Malaysia that lead to baby trafficking problems. / Jr Thaddeus Jack Kinabalu, Nasyrah Ezzan Ali and Nurizzati Ali - Kinabalu, Jr Thaddeus Jack; Ali, Nasyrah Ezzan; Ali, Nurizzati (2013)
High demand for babies for adoptions contributes to increasing cases of baby trafficking in our country. The adoption process in our country may takes at least two years for it to be legalised by the court. The long and complicated procedure to adopt babies forced some parents to opt for illegal means of getting adopted children that is through the syndicate of baby trafficking. In addition, lacked of assisting agencies that can provide babies for legal adoption makes the situations worsen. There are several interviews which have been conducted to obtain information regarding this matter. The target groups of interviewees chosen were the National Registration Department, the Welfare Department and OrphanCARE. In this research, our group are trying to propose to the policy maker to make a review on the current adoption law. Besides that, we also think that more adoption agencies shall be made into existence so as to help the government in making the legalisation of adoption process be made easier and less complicated. From this research we may also see how the laws on adoption in other developed countries such as the United States and England are different from what we have in our country especially in the period taken in making the adoption legal. At the end of this research paper, some recommendations are made to assist the policy maker in reviewing and amending the current law on adoption and for the betterment of the public at large.